Instrumentação de linha de produção de dispositivos sensores baseados em nanofitas semicondutoras - Pedersoli, André Aleixo (Universidade Federal de São Carlos, 2023)
This work describes the stages of the photolithography process of electronic devices to study their electrical properties. properties developed in a semiconductor physics research laboratory. The optimization and automation of a photosensitivity device used in photolithography techniques are described. Automation was done using an Arduino Uno microcontroller and servomotors. The project was tested with the aim of reducing failures due to operational errors and seeking to improve safety in the production of devices involving ultraviolet radiation.
Instrumentation of semiconducting nanobelts sensor devices production line
Keywords: Fotolitografia; Arduino; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA DA MATERIA CONDENSADA::ESTRUTURAS ELETRONICAS E PROPRIEDADES ELETRICAS DE SUPERFICIES INTERFACES E PELICULAS